The Effect of Land Clearing Techniques on the Chemical and Biological Character of Soil in Sugarcane Fields - Anna Kusumawati; Lintang Panjali Siwi Pambayun (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Land clearing after harvest in sugarcane cultivation is often done by burning. However, burning influences the ecosystem, such as the chemical and biological characteristics of soil. This research aims to analyze the impact of different methods of clearing sugarcane fields on the chemical and biological conditions of the soil. This research used a non-factorial, completely randomized design (CRD) with two treatments: land clearing with burning and without burning. Each treatment was carried out on an area of 50 m2 with two blocks as repetitions. For chemical and biological analysis, soil samples were taken from pitfall traps and soil monoliths (1 m x 1 m x 30 cm). Two treatments showed significant differences in the total N and available P, and burning reduced 21% the number of organisms significantly. There were significant differences between the two treatments regarding the macrofauna diversity index, species evenness value, and dominance index. Post-harvest burning significantly reduces total N and available P and negatively impacts biological indicators such as organism numbers, diversity, evenness, and dominance index. This decrease in organic matter causes a reduction in the populations of organisms, thus disrupting soil health. Therefore, this study recommends that sugarcane residues be returned to the land as a source of organic matter to maintain soil health, biodiversity, and optimal productivity.